Recently exposed vegetation reveals Holocene changes in the extent of the Quelccaya Ice Cap, Peru - Buffen, Aron M.; Thompson, Lonnie G.; Mosley-Thompson, Ellen; Huh, Kyung In (QUATERNARY RESEARCH, 2009)
Radiocarbon dating of well-preserved, in-place vegetation exposed by the retreating Quelccaya Ice Cap of southeastern Peru constrains the last time the ice cap's extent was smaller than at present. Seventeen plant samples from two sites along the central western margin collectively date to 4700 and 5100 cal yr BP and strongly indicate that current ice cap retreat is unprecedented over the past similar to 5 millennia. Seventeen vegetation samples interbedded in a nearby clastic sedimentary sequence suggest ice-free conditions at this site from similar to 5200 to at least similar to 7000 cal yr BP, and place minimum constraint on early- to mid-Holocene ice cap extent. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
Keywords: 14C dating; Andes; Climate change; Glacier retreat; Holocene; Peru; Quelccaya Ice Cap; South America; Tropical glaciers